Customs Exemptions Law with its Executive Regulations modified up to jan 1999 = قانون الإعفاءات الجمركية ولائحته التنفيذية / presidency - Egypt. presidency (2025)
Law No 186 for 1986: Promulgating for organizing customs exemptions – Decree No. 193 for 1986: issuing the executive statutes for the decree of the President of the Republic no. 186 of 1986 promulgating the law regulating customs exemptions